Manufacturing technology of integrated textile-based sensor networks for in situ monitoring applications of composite wind turbine blades. (16th September 2016) - Haentzsche, Eric; Mueller, Ralf; Huebner, Matthias; Ruder, Tristan; Unger, Reimar; Nocke, Andreas; Cherif, Chokri
Abstract: Based on in situ strain sensors consisting of piezo-resistive carbon filament yarns (CFYs), which have been successfully integrated into textile reinforcement structures during their textile-technological manufacturing process, a continuous load of fibre-reinforced plastic (FRP) components has been realised. These sensors are also suitable for structural health monitoring (SHM) applications. The two-dimensional sensor layout is made feasible by the usage of a modular warp yarn path manipulation unit. Using a functional model of a small wind turbine blade in thermoset composite design, the sensor function for basic SHM applications (e.g. static load monitoring) are demonstrated. Any mechanical loads along the pressure or suction side of the wind turbine blade can be measured and calculated via a correlative change in resistance of the CFYs within the textile reinforcement plies. Performing quasi-static load tests on both tensile specimen and full-scale wind turbine blade, elementary results have been obtained concerning electro-mechanical behaviour and spatial resolution of global and even local static stresses according to the CFY sensor integration length. This paper demonstrates the great potential of textile-based and textile-technological integrated sensors in reinforcement structures for future SHM applications of FRPs.